Experimental research into leaching of metals from immobilized CIS solar module waste. Issue 4 (1st October 2016) - Vasarevičius, Saulius; Skripkiūnas, Gintautas; Danila, Vaidotas
Abstract: The aim of this research is to determine metal leaching from concrete specimens containing different quantities of waste recovered from copper indium selenide (CIS) solar module by replacing a certain share of sand aggregate. During the first stage of research the CIS solar module was shredded and leaching tests were performed on recovered waste by analysing six metals – Na, Mg, Fe, Cd, Cu and Zn. It has been determined that out of all metals analysed, the highest leaching was observed for sodium, while the highest leaching out of the heavy metals was found for zinc. In Phase II of the study concrete specimens with shredded CIS module waste were made and the physical properties of these specimens as well as the leaching of the same metals was determined. The results have shown that three metals, namely Fe, Cd, Zn, were successfully immobilised and did not leach from the specimens.